2006
DOI: 10.1007/s00198-006-0087-0
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in degree of mineralization and enzymatic collagen cross-links and increases in glycation-induced pentosidine in the femoral neck cortex in cases of femoral neck fracture

Abstract: These results suggest that reductions in the degree of mineralization and enzymatic cross-links and excessive formation of pentosidine may play an important role in explaining poor bone quality in osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(143 citation statements)
references
References 56 publications
8
131
2
2
Order By: Relevance
“…Its accumulation is associated with age-related degradation in the mechanical properties of bone (17,23). Pentosidine levels are higher in the bones of patients with femoral neck fractures compared with age-matched controls (24,25). Serum pentosidine concentrations were positively correlated with the radiographic severity of lumbar spondylosis in a crosssectional study involving Japanese subjects (26).…”
Section: Discussionmentioning
confidence: 99%
“…Its accumulation is associated with age-related degradation in the mechanical properties of bone (17,23). Pentosidine levels are higher in the bones of patients with femoral neck fractures compared with age-matched controls (24,25). Serum pentosidine concentrations were positively correlated with the radiographic severity of lumbar spondylosis in a crosssectional study involving Japanese subjects (26).…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies found that higher levels of AGEs are associated with decreased postyield properties of cortical and trabecular bone. 23,24,29,58 Moreover, in trabecular bone from human femora, Tang et al 27 reported a negative relationship between PEN and postyield mechanical properties, but no association with preyield properties. We did not evaluate postyield properties in this study because they are problematic for compression tests since the trabecular bone compresses upon itself, thus our finding that PEN was not associated with mechanical properties is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In human, osteoporotic bones, which exhibit decreased quantity and impaired mineralization of bone, have shown lower content of collagen 18,19) and higher extent of Lys hydroxylation [19][20][21][22] be partly damaged compared to those from fresh bone. However, the contents of collagen (average of 125~128 ìg/mg of dried bone)…”
Section: Discussionmentioning
confidence: 99%